Pelatihan Pembuatan Alat Permainan Edukatif Untuk Meningkatkan Perkembangan Aspek Sosial Anak Usia Dini - Musafir, Musafir; Pamuji Rahayu, Eka; Fatihaturrahmi, Fatihaturrahmi (Jurnal Pengabdian Masyarakat Sains Indonesia (Indonesian Journal Of Science Community Services), 2021)
This article discusses the importance of training in making educational game tools in supporting the development of social aspects of early childhood. With increasing awareness of the role of play in children's learning processes, this research aims to explore how educational play tools can be designed and implemented to increase social interaction among children. Through structured training methods, it is hoped that educators and parents can better understand how to create a play environment that supports children's social development. The results of this training show a significant increase in children's social abilities, including communication and collaboration skills.